(3GdRgO GdcHjQs - (3CHh HcQ CMeO Hf GdMSjf Hf Ydj GdNQGSGfj GdTGaYj, GdHjgbj,J (B458 (3g` s ((3OeTb s)
(3ChdgG (B:s
(3CeG HYO abO PcQJ ai cJGH GdLGeY ai HGH GdRgO HYV eG MVQfi ef GdCNHGQ hGdBKGQ ai GdRgO hbUQ GdCed s
(3BNQgG (B:s
(3bGd QShd Gddg Udi Gddg Ydjg hSde (B( (3djS GdNHQ cGdeYGjfI Ef Gddg NHQ ehSi HeG UfY bheg ai GdYOd ade jdb GdCdhGM adeG YGjf eG UfYhG Cdbi GdCdhGM (B) (3BNQ cJGH GdRgO GdcHjQ hGdMeO ddg hMOg s
(3GdfSNI HgG MhGTs
(3Ydjg YOg SeGYGJs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B116 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B1 - (3U (B206s
Keywords: (3GdMOjK h GdeUWdMs